An Experimental Investigation of the Effect of Cost Information and Feedback on Product Cost Decisions* - GUPTA, MAHENDRA; KING, RONALD R. (Contemporary Accounting Research, 1997)
In this paper we report the results of an experiment designed to investigate the potential benefits of more accurate costing systems. Subjects in our experiment participated in one of four single‐person decision making settings, which varied in terms of the accuracy of costing systems (less accurate versus more accurate cost reports) and in the complexity of the economic environment (less heterogeneous versus more heterogeneous products). The costing systems provided imperfect reports that subjects could use to select forecasts of future product costs. Forecast accuracy determined the resulting payoffs for subjects. In addition to having the cost reports when making forecasts, subjects also observed the association between forecasts and actual profits for previous periods and the rank ordering of the products' relative usage of resources at each of the production processes. The results from our experiment indicate that subjects did not select forecasts based only on reported costs. Rather they updated forecasts using profit feedback and the supplemental rank information about the products' relative usage of resources. We found that profits decreased as the complexity of economic environment increased but increased with the accuracy of cost reports. The profits associated with less accurate costing systems, however, were not as low as we would have predicted had the subjects used the cost reports as their forecasts. In fact, using profit feedback, subjects were able to converge toward optimal profits even with imperfect cost information.